Edukasi Makanan Risiko Rendah Karies Pada Ibu-Ibu di Ruang Publik Terpadu Ramah Anak Harapan Mulia Jakarta Pusat - Okky Marita Ardy; Fathimah Azzahra Attamimi; Nur Hidayati Nosi; Alisa Novianty Pratiwi; Dharma Satya Aprianto (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The results of the 2018 Riskesdas stated that 93% of young children have dental caries. One of the reasons is provision of food and drinks that cause caries. A mother has a major role in caring of children, such as teach healthy habits because children often imitate the adults. This education can help reduce the risk of dental caries in the family and increase awareness about the important role of food in dental health. This activity was carried out at RPTRA Harapan Mulia, Central Jakarta, with the aim of increasing mothers' knowledge about foods with low caries risk. The methods used include counseling using educational books about foods and drinks that are good for teeth, toothbrushes, and oral dental examinations. The results showed that there was a statistically significant difference P <0.05 regarding knowledge before and after being given education. Educational books make it easier for participants to catch information.